The Itinerant University of the Sea, a Platform for the Knowledge Geographic of the World Today. - Rodríguez-Gutiérrez, Fermín (Revista de Estudios Andaluces, 2017)
The Itinerant University of the Sea was created in 2006 by the universities of Oviedo, Porto and the Naval School of Lisbon, to provide a training experience that has as its horizon to awake the mind of the young people and not sleep it, using the sea as a way and a ship of instruction as a tool in order to extend the personal skills of the participants, by applying the phrase "knowledge and adventure" as a basic descriptor of the teaching of geography. Here we explain why, how and what it does.